Da'wah Understanding and Activity among the Society of Kampung Desa Taqwa, Gemang, Kelantan - Fatimah Bt Ismail (Universiti Sains Islam Malaysia, 2009)
This project paper will be discussed about da'wah understanding and activity among the society of Desa Taqwa Kampung Gernang, Kelantan. In the project paper the writer discussed the whole concept of da'wah Islamiyyah as a role of efficient in da'wah and an example for spreading da'wah Islamiyyah to Muslim. The selected area of research is Kampung Gemang because their resident have big potential to become an Islamic propagator. Many activities have been executed in this village. There are Islamic speech, increase of economy society agriculture, welfare and others, until the Kampung Gemang is declared as Kampung Desa Taqwa by local government.